The Effect of Partnership Strategy on Competitive Advantages through the Market Area and Health Services’ Innovation: (A STUDY AT Dr. F.X SUHARDJO NAVY HOSPITAL LANTAMAL IX AMBON) - Hisnindarsyah,; Budiyanto,; Khuzaini, (International Journal of Scientific Research and Management (IJSRM), 2020)
Based on the 2014 Indonesia Republic Minister of Health Regulation on Hospital Licensing Classification, it is explained that the Hospital is one of the bodies engaged in the health sector which plays an important role for the creation of quality of life and the environment for the community, so as to create a high degree of health both for physical, spiritual health , and social. The attention of the Head of F.X Suhardjo Navy Hospital to the partnership strategy towards competitive advantage. This may improve the ability of the Head of F.X Suhardjo Navy Hospital to develop appropriate strategies to further enhance his competitive advantage. Health service innovation has an effect on competitive advantage, useful for F.X Suhardjo Navy Hospital heads in the sense that they can make efforts to improve health service innovation to improve their competitive advantage.